Context and practices of health advocacy role by nurses in Ghana: A qualitative study - Luke Laari (Nursing Practice Today)
Background & Aim: Nurses play a crucial role in health advocacy, which is both morally obligatory and has significant consequences for the clinician. However, there is a paucity of empirical evidence regarding its context and practices. The location, method, and rationale behind nurses fulfilling their health advocacy duties are crucial in hospital settings. This study explored and described where and under what circumstances nurses fulfill their health advocacy responsibilities in Ghana. Methods & Materials: The study employed an inductive qualitative exploratory descriptive design to gather and analyze data from 24 nurses and midwives. Using a semi-structured interview guide, participants were selected from three regional hospitals in the upper, middle, and southern zones of Ghana, and qualitative content analysis was performed. Results: Nurses and midwives carried out their health advocacy roles both inside and outside of healthcare institutions, using both proactive and reactive advocacy practices to initiate their role performance. Although reactive advocacy roles were reported more, the nurses and midwives identified unfair client treatment, health professionals' errors or omissions of procedure, and social injustice as the driving forces behind their advocacy. Conclusion: Although health advocacy is performed by both nurses and midwives in hospitals and outside the hospitals, they are mostly reacting to situations. Teaching biopsychosocial assessment techniques to students during training and providing them with coaching and mentoring during clinical practice may enhance their ability to assess clients for unmet advocacy needs, enabling them to be proactive in their role performance.